If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2 + 2x) = -24 (2 * -6 + 2x * -6) = -24 (-12 + -12x) = -24 Solving -12 + -12x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -12x = -24 + 12 Combine like terms: -12 + 12 = 0 0 + -12x = -24 + 12 -12x = -24 + 12 Combine like terms: -24 + 12 = -12 -12x = -12 Divide each side by '-12'. x = 1 Simplifying x = 1
| .50x+8=3x+5 | | 0=(-4x^2-6x)-1 | | 8x+7=3x+3 | | 671.5=174.5+35.5(x-1) | | 43000=a-140000 | | x/6+94-76=31 | | 5x-40=17 | | 2x-33+5x= | | w=2d+7 | | 4x+8-7x=-1 | | 2(-c-8)=-2c-8 | | 3y(8)=6y | | 32-12.50x=400 | | 5x+4+3x+9=61 | | 671.5=139x+35.5 | | 110000-40000=N | | 3+5y=5-7y | | 17=5x-40 | | 9x+5+9x+3=170 | | y^2(y^2-5)-36=0 | | -7x+7=-4 | | 95=s-385 | | -7=514a | | 3x+3+9x+7=94 | | 85=s-385 | | -1=-6x+5x+4 | | -7x=11 | | -100=-2+7(4n+6x) | | (X+0.7)(x+3.4)=0 | | (x+1)(4x-3)=2(x+1)(2x+3) | | 12600-s=925 | | 8x+8+6x+6=56 |